Miasmatic Study of Cervical Spondylosis (Advancements in Homeopathic Research, 2022)
Chronic cervical spondylosis is very common now a days due to the lifestyle most people lead. Well diagnosed cases of Cervical Spondylosis have been treated at P.D. Jain Homoeopathic Medical College, Parbhani, (M S). Cases of Cervical spondylosis was treated along with miasmatic background where many of the degenerative changes are completely recovered. Selection of medicine was done on totality and by repertorizing rubrics obtained from Life space investigation , signs & symptoms with special emphasis on miasmatic background, antimiasmatic medicine was prescribed and dispensed in different potencies. Follow up of the cases was done and repetition was based on the response of the patient for the first prescription.
Keywords: Cervical Spondylosis; Miasm; Psora; Syphilis; Sycosis; Totality of Symptoms